Red fluorescence protein (DsRed2) promotes the screening efficiency in peanut genetic transformation - Huai, Dongxin; Wu, Jie; Xue, Xiaomeng; Hu, Meiling; Zhi, Chenyang; Pandey, Manish K.; Liu, Nian; Huang, Li; Bai, Dongmei; Yan, Liying; Chen, Yuning; Wang, Xin; et al. (Frontiers in Plant Science, 2023)
Peanut (Arachis hypogaea L.), one of the leading oilseed crops worldwide, is an important source of vegetable oil, protein, minerals and vitamins. Peanut is widely cultivated in Asia, Africa and America, and China is the largest producer and consumer of peanut. Genetic engineering has shown great potential to alter the DNA makeup of an organism which is largely hindered by the low transformation and screening efficiency including in peanut. DsRed2 is a reporter gene widely utilized in genetic transformation to facilitate the screening of transformants, but never used in peanut genetic transformation. In this study, we have demonstrated the potential of the red fluorescence protein DsRed2 as a visual reporter to improve screening efficiency in peanut. DsRed2 was firstly expressed in protoplasts isolated from peanut cultivar Zhonhua 12 by PEG, and red fluorescence was successfully detected. Then, DsRed2 was expressed in peanut plants Zhonghua 12 driven by 35S promoter via Agrobacterium tumefaciens-mediated transformation. Red fluorescence was visually observed in calli and regenerated shoots, as well as in roots, leaves, flowers, fresh pod shells and mature seeds, suggesting that transgenic screening could be initiated at the early stage of transformation, and continued to the progeny. Upon screening with DsRed2, the positive plant rate was increased from 56.9% to 100%. The transgenic line was then used as the male parent to be crossed with Zhonghua 24, and the hybrid seeds showed red fluorescence as well, indicating that DsRed2 could be applied to hybrid plant identification very efficiently. DsRed2 was also expressed in hairy roots of Huayu 23 via Agrobacterium rhizogenes-mediated transformation, and the transgenic roots were easily selected by red fluorescence. In summary, the DsRed2 is an ideal reporter to achieve maximum screening efficiency and accuracy in peanut genetic transformation.